MOLECULAR-GENETIC CERTIFICATION OF POTATO VARIETIES AND FORMS USING SSR-MARKERS - Yessimseitova , A.K.; Shustov , A.V.; Ahmetollaev , I.A.; Krassavin , V.F. (Eurasian Journal of Applied Biotechnology, 2015)
In recent years, the problem of identification of species and varieties of potatoes is gaining importance due to the accelerated breeding process and the emergence of many new forms. Particular attention is paid to the development of effective methods that can be used in variety trials, breeding, seed production, and control of seed. The high level of polymorphism detected using SSR-markers establishes the potential of this marker system and suggests the possibility of its use to evaluate genetic variation between clones and varieties of potato, as well as fast and reliable identification of varieties.